A comparison of different definitions of metabolic syndrome for the risks of atherosclerosis and diabetes - Tsai, Sung-Sheng (Diabetol Metab Syndr, 2018)
BACKGROUND: The reported outcomes of the metabolic syndrome (MetS), containing atherosclerotic cardiovascular disease and diabetes, vary according to the definitions used. This study was designed to compare the performance of the Adult Treatment Panel III/American Heart Association/National Heart, Lung, and Blood Institute (ATP III/AHA/NHLBI) and International Diabetes Federation (IDF) criteria for the risks of atherosclerosis and diabetes. METHODS: We sifted subjects from a self-paid Health examination program from 1999 to 2015 in this cross-sectional population-based study. On the basis of the ATP III/AHA/NHLBI and IDF criteria, the MetS diagnosis and scores were concluded. A brachial-ankle pulse wave velocity (baPWV) more than or equal to 1400 cm/s indicated more severe arterial stiffness, and a high fasting glucose level more than or equal to 6.99 mmol/L or postprandial glucose level more than or equal to 11.10 mmol/L indicated diabetic-level hyperglycemia. Comparisons of the areas under receiver operating characteristic curves (AUC–ROC) for both MetS scores to correlate with a higher baPWV and diabetic-level hyperglycemia were evaluated. RESULTS: In the 26,735 enrolled subjects with an average age of 55 (± 12) years, 6633 and 7388 (24.8% vs. 27.6%, p < 0.001) were classified as having MetS on the basis of the ATP III/AHA/NHLBI and IDF criteria, respectively. The AUC–ROC for the ATP III/AHA/NHLBI-MetS score were higher than those for the IDF-MetS score (0.685 vs. 0.595 to correlate with a higher baPWV, p < 0.001; 0.791 vs. 0.665 to correlate with diabetic-level hyperglycemia, p < 0.001). CONCLUSIONS: To the best of our knowledge, this is the first study to demonstrate that through a holistic approach, the performance of the ATP III/AHA/NHLBI-MetS score for the risks of atherosclerosis and diabetes was superior to the IDF-MetS score for Asians.